PENGARUH SUPERVISI DAN DUKUNGAN TUGAS (TASK SUPPORT) TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SMP NEGERI DI KABUPATEN HALMAHERA SELATAN PROVINSI MALUKU UTARA - Halifat Wahid (Universitas Negeri Jakarta, 2014)
The objective of the reserach was to find out the influence from supervision and Task-Support toward organizational citizenship behavior (OCB) of Teachers. The research took place at State Junior High School of South Halmahera, North Maluku Province.. The Research used random sampling and path analysis as its technical ways. The sample of the research were 91 teachers of state Junior High School. The result of the reserach showed that supervision has positif effect (1) supervision has direct effect to orgnizational citizenship behavior (OCB), (2) task support has positif effect to organizational behavior (OCB), (3) supervison has positif direct effect to task support. Therefore, The Research concluded that organizational citizenship behavior (OCB) teachers could upgrade themselves well if the supervison could work great and supported by qualified task support.